ANALISIS PENGENDALIAN KUALITAS OIL LOSSES PADA PROSES PEREBUSAN MENGGUNAKAN QUALITY CONTROL CIRCLE PADA INDUSTRI PENGOLAHAN KELAPA SAWIT DI SUMATERA BARAT - Kharnofa, Fuji; Maryam, Maryam (Politeknik ATI Padang, 2022)
One of the palm oil processing industries in West Sumatra has raw materials in the form of fresh fruit bunches that come from their own farms and the community. In the processing process, there is a problem of loss of palm oil in the production process. This will affect the quality of the product, so the quality in the production process needs to be controlled, which is boiling. Based on the results of preliminary observations, the boiling station experienced loss of palm oil in condensate water discharge and loss of palm oil in empty bunches. Loss of palm oil in empty bunches is set as a standard of <0.129% by the company. The analysis will be carried out related to quality control, especially in the boiling process of one of the Palm Oil Mills in Sumatra using the QCC (quality control circle) method. From the results of the Quality Control Circle analysis, it can be seen that boiling time and boiling pressure greatly affect the loss of palm oil. The longer the boiling time, the greater the loss of palm oil, while the lower the boiling pressure, the greater the loss of palm oil. There are several factors that cause the loss of palm oil in the boiling process, including machines, people, raw material factors and methods. The machine factor is the main factor because the sterilizing machine cannot operate optimally until the required pressure is not reached.